Combination Pod-Intravaginal Ring Delivers Antiretroviral Agents for HIV Prophylaxis: Pharmacokinetic Evaluation in an Ovine Model - Moss, John A. (Antimicrob Agents Chemother, 2016)
Preexposure prophylaxis (PrEP) against HIV using oral regimens based on the nucleoside reverse transcriptase inhibitor tenofovir disoproxil fumarate (TDF) has been effective to various degrees in multiple clinical trials, and the CCR5 receptor antagonist maraviroc (MVC) holds potential for complementary efficacy. The effectiveness of HIV PrEP is highly dependent on adherence. Incorporation of the TDF-MVC combination into intravaginal rings (IVRs) for sustained mucosal delivery could increase product adherence and efficacy compared with oral and vaginal gel formulations. A novel pod-IVR technology capable of delivering multiple drugs is described. The pharmacokinetics and preliminary local safety characteristics of a novel pod-IVR delivering a combination of TDF and MVC were evaluated in the ovine model. The device exhibited sustained release at controlled rates over the 28-day study and maintained steady-state drug levels in cervicovaginal fluids (CVFs). Dilution of CVFs during lavage sample collection was measured by ion chromatography using an inert tracer, allowing corrected drug concentrations to be measured for the first time. Median, steady-state drug levels in vaginal tissue homogenate were as follows: for tenofovir (TFV; in vivo hydrolysis product of TDF), 7.3 × 10(2) ng g(−1) (interquartile range [IQR], 3.0 × 10(2), 4.0 × 10(3)); for TFV diphosphate (TFV-DP; active metabolite of TFV), 1.8 × 10(4) fmol g(−1) (IQR, 1.5 × 10(4), 4.8 × 10(4)); and for MVC, 8.2 × 10(2) ng g(−1) (IQR, 4.7 × 10(2), 2.0 × 10(3)). No adverse events were observed. These findings, together with previous pod-IVR studies, have allowed several lead candidates to advance into clinical evaluation.